Analisis Pengaruh Karakteristik Perusahaan Terhidap Pengungkapan Tanggung Jawab Sosial Perusahaan dalam Laporan Tahunan Perusahaan Manufaktur yang Terdaftar di BEI Periodie 2009-2010 - Erna Hidayah; Windi Pamungkas (Jurnal Aplikasi Bisnis, 2017)
This study aimed to analyze the effect offirm characteristcs on the disclosure ofcorporate social responsibility. The characteristics are proxied by the management ownership, leverage, size of the company and the profitability. While the disclosure of corporate social responsibility is proxied by CSR Index. The samples of thisresearch were 48 manufacturing companies. Based on the hypothesis test, it was found that ownership management and profitability did not significantly affect the disclosure of corporate social responsibility while leverage variable and firm size significantly affected the disclosure ofcorporate social responsibility.